Determination of Total Flavonoid Contents of The Antioxidant Herbal Beverage Caesalpinia sappan L. Quantitatively Using The Calorimetry Methods of The AlCl3 Reaction That Forms Complex Compounds - syahdam karneng, syahdam karneng (Hayyan Journal, 2024)
Body health is an important thing, so many choices of methods for maintaining body fitness are offered. One way is to consume herbal plants that contain antioxidant compounds. Antioxidant compounds can neutralize and prevent damage caused by free radicals in the body. The plant that contains high antioxidant compounds is secang (Caesalpinia sappan L.). In previous research, a test of the antioxidant activity of this plant with an IC50 value of 11.37 ppm was reported, but a test to determine the total flavonoid content of the compound had never been carried out. So, this research is interesting to carry out with the aim of finding out the total flavonoid levels in a serving size of 0.05 grams of secang powder. The method for determining total flavonoid content used is the calorimetry method with AlCl3 reagent as a complex compound forming and quantitative analysis using an Ultraviolet Visible (UV-Vis) spectrophotometer. The flavonoid content value obtained was 0.2370% b/b for a serving size of 0.05 grams of sample. These results indicate that the secang sample contains flavonoid compounds which can be useful for increasing the body's immunity.